Investigating the Relationship between Parental Punishment and Academic Achievement: A Case Study of Secondary Level Students in Sargodha, Pakistan - Mushtaq Ahmad; Khalid, Muhammad Naveed; Taskeen Zafar (UMT Education Review, 2022)
The current study explored the link of parental punishment with academic achievement of secondary school students. The sample size of 400 students (200 male and 200 female) was conveniently selected from both the private and the public secondary schools of tehsil Sargodha. A self-developed questionnaire was used to collect data. The collected data were analyzed through descriptive statistics. Major findings included that the majority of the students were physically punished. Whereas, some students were psychologically and emotionally punished by their parents. The results showed that parental punishment causes low academic achievement among students. The current study recommended that parents should not punish their children as it ultimately lowers their academic performance outcomes. This practice of parental punishment may be discouraged by guiding the parents in parent-teacher meetings.